'Team ethnography visual maps': Methods for identifying the ethnographic object in multiple sites of fieldwork. (December 2021) - Parkin, Stephen; Locock, Louise; Montgomery, Catherine; Chisholm, Alison
Team ethnography is becoming more popular in research. However, there is currently limited understanding of how multiple ethnographers working together actually share their experiences of conducting team ethnography. There is also an associated lack of explanation regarding how evidence and conclusions are drawn from such collective endeavour. This article attempts to address this absence of detail regarding the practice and conduct of team ethnography. In the following account, the authors present details of the design, development and application of 'team ethnography visual maps' and the collaborative reflexivity that took place within 'team ethnography data sessions' that were each embedded within a mixed methods study of frontline services located in six different National Health Service Trusts throughout England (UK). After a presentation of the ethnographic methods and analyses that occurred as part of team ethnography, they are then discussed in terms of their applied and academic value from a methodological perspective.